PENGARUH JOB DESCRIPTION TERHADAP PRESTASI KERJA KARYAWAN PADA PT KRAKATOA LAMPUNGTOURISM DEVELOPMENT (GRAND ELTTY KRAKATOA HOTEL AND RESORT) KALIANDA - Soadin Soadin (Jurnal Ilmiah Ekonomi Manajemen: Jurnal Ilmiah Multi Science, 2017)
This study focuses on the process of the job description and job performance on the provider PT. Krakatoa Lampung Tourism Development (Elty Krakatoa Grand Hotel And Resort) Kalianda, which is a provider Hotel and Resort which has the advantage. However, the hotel and resort provider also has many competitors who are ready to compete to win consumers. The reason underlying this research topic is that each provider Hotel and Resort in defending consumers or customers, must have good employees in accordance with the job description and employee performance. This study aims to determine the effect of the job description on employee performance. This research was conducted at PT. Krakatoa Lampung Tourism Development (Elty Krakatoa Grand Hotel And Resort) Kalianda, the number of respondents that used in this study sample were 26 respondents. The research method used is a survey method with descriptive research, with a quantitative approach. The result of the discussion explains that a simple linear regression equation y = 0.305 + 1,360X meaningful job description and significant positive effect on employee work performance, if the variable X is increased by one point will improve the performance of 1,360 units of the unit and if there is no job description for the job performance employees totaled 0,305 a unit. Results of correlation analysis that the Job Description (X) with employee performance (Y) of rxy = 0.781 in the category of "correlated", with the effect of 61.1% and of 38.9% is affected by factors beyond the job description and work performance. The results of t-test analysis (ttest) (α = 0.05), t-test: 6.134 t-table: 2.064, then thank Ha: there is a significant effect of the job description on employee performance.